Papillary Carcinoma of Thyroid in a Child, Rare but Aggressive: A Case Report - Regmi, Pradeep R; Amatya, Isha; Paudel, Sharma; Kayastha, Prakash (Journal of Institute of Medicine Nepal, 2021)
Thyroid nodules are uncommon in childhood than adult population. Thyroid malignancies are more common in the detected nodules comprising 22-26% in paediatric age groups in comparison to 5-15% of the adult population. In addition, thyroid malignancies are more aggressive in children than in adults with nodal and pulmonary metastasis. Despite having more recurrent rate than in the adults, survival seems to be better. We are presenting a case of an 11-year-old child presented to our clinic with swelling of neck for 3 months duration. Diagnosis was made through ultrasound, computed tomography and histopathological analysis. Therefore, diagnosing a case with papillary carcinoma of thyroid in children is very challenging and demanding the expertise. Paediatric radiologist could play a vital role in diagnosis which leads to proper management.